Fecal calprotectin predicts complete mucosal healing and better correlates with the ulcerative colitis endoscopic index of severity than with the Mayo endoscopic subscore in patients with ulcerative colitis - Sun-Ho Lee; Min-Ju Kim; Kiju Chang; Eun Mi Song; Sung Wook Hwang; Sang Hyoung Park; Dong-Hoon Yang; Kyung-Jo Kim; Jeong-Sik Byeon; Seung-Jae Myung; Suk-Kyun Yang; Byong Duk Ye (BMC Gastroenterology, 2017)
Abstract Background We aimed to evaluate the role of fecal calprotectin (FC) as a noninvasive marker for the disease activity of ulcerative colitis (UC) in a Korean cohort. Methods A total of 181 fecal samples were collected from 181 consecutive UC patients between April 2015 and September 2016. FC levels were measured using the Quantum Blue® Calprotectin rapid test. The laboratory test results, partial Mayo Score (pMS), and colonoscopic imaging findings at FC level measurement were retrospectively reviewed. The Mayo endoscopic subscore (MES) and UC endoscopic index of severity (UCEIS) were graded by 2 certified endoscopists after training with 50 other cases. Results The FC levels were significantly correlated with pMS (Spearman correlation coefficient r = 0.428, p < 0.001), MES (r = 0.304, p < 0.001), UCEIS (r = 0.430, p < 0.001), and CRP (r = 0.379, p < 0.001). FC levels exhibited a significantly better correlation with UCEIS than with MES (Meng’s z = − 2.457, p = 0.01). The FC cut-off level of 187.0 mg/kg indicated complete mucosal healing (MES = 0; UCEIS =0) with a sensitivity and specificity of 0.857 and 0.891, respectively (area under the curve, 0.883; 95% confidence interval, 0.772–1.000). Conclusion The FC level is significantly correlated with the clinical disease activity index, endoscopic indices, and serum inflammatory biomarkers in a Korean UC cohort. FC is highly predictive of complete mucosal healing in UC. UCEIS exhibits a stronger correlation with the FC level, as compared to MES. Thus, FC could be used as a reliable noninvasive indicator for evaluating disease activity and mucosal healing in UC.